Keberkesanan modul multimedia interaktif dalam meningkatkan kefahaman pelajar sekolah menengah terhadap topik pembahagian sel - Ahmad Mokhtar, Muhanizah (2006)
A study has been carried out to produce an interactive multimedia module to enhance secondary school students understanding in ‘cell division’. The objective of this study is to determine the effectiveness of the module, as a better enrichment material compared to a conventional way. One hundred and fifty students of four different secondary schools in Kuala Kangsar were involved in this study. The students were divided into three groups randomly and were given two sets of questions on ‘cell division’ as a pre and post test. Then they were given different enrichment material according to group. First group (n=50) explored the interactive multimedia module, second group with the reference notes (n=50) and third group as the control group (n=50). The results of the study showed the group which used interactive multimedia module scored better result among the three groups [p<0.05]. However, the result of the study showed only two subtopics had a significant result which is , cell cycle and meiosis.